Students as co-designers in health professional education: a scoping review - Élodie Ambrosetti; Cyrille Gaudin; Simon Flandin; Germain Poizat (BMC Medical Education)
Abstract Background Over the last thirteen years, there has been a notable increase in both research and practice related to student-staff partnerships in higher education. However, within health professional education (HPE), studies on these partnerships remain limited and often rely on broader higher education frameworks. Existing research primarily focuses on role dynamics and relational aspects rather than on structured co-design processes, where students actively contribute to shaping educational content, assessments, or curricula. Building upon previous work, this study specifically examines co-design as a distinct dimension of student-staff partnerships in HPE, an area that has not been thoroughly addressed in recent literature reviews. Methods In accordance with the PRISMA-ScR 2018 statement, we performed searches in online databases—Cochrane, Ovid, PubMed, ScienceDirect, and Scopus—for original articles published in English from 2010 to 2023. These articles needed to describe empirical studies focused on co-designed training programs in health professions. We then conducted a qualitative and descriptive analysis of the selected articles to examine how the principle of students as co-designers is portrayed and investigated in health professional education. Results The search (title, abstract, keywords) identified 703 potentially relevant abstracts addressing co-design in healthcare education. Screening of these abstracts narrowed it down to 84 articles. Further evaluation of these full articles resulted in a final sample of 20 articles that met the inclusion criteria. We analyzed the content of these 20 articles using the following categories: basic characteristics (year of publication, country, professional domain, educational grade, topic of the training), co-design characteristics (context and initiative, framework and definition, purposes, stakeholders, process), and study characteristics (aim, research framework, population, data collection and analysis, key findings). Our analysis revealed that co-design in HPE lacks standardized frameworks and rigorous empirical evaluation. Many studies emphasize student contributions but do not provide detailed methodological guidance on how co-design is structured, implemented, or assessed. Additionally, findings indicate that most studies focus on undergraduate education, with postgraduate applications remaining underexplored. Conclusions This review underscores co-design as an emerging yet underdeveloped approach in health professional education. While its potential benefits—such as enhancing student engagement, fostering innovation, and improving training relevance—are widely acknowledged, the field lacks structured methodologies and theoretical grounding. Future research should focus on developing clear frameworks, assessing co-design’s long-term impact on learning outcomes, and differentiating it from broader collaborative approaches. Strengthening methodological rigor and empirical validation will be essential for positioning co-design as a sustainable and evidence-based practice in health professions education.